Kontribusi dan Motivasi Keluarga Korban Bencana Sigi dalam Beternak Ayam KUB Bantuan BALITBANGTAN - Mardiana Dewi; Masyitah Muharni; Wardi Wardi; Heni Sulistyawati Purwaning Rahayu (Jurnal Ilmu Peternakan Terapan)
The natural disasters of the earthquake, liquefaction, and tsunami that occurred on September 28, 2018 in Palu, Sigi, and Donggala have caused damage and even loss of residence and property of the people in the region. Agricultural land which was a source of livelihood could not be reused. During the recovery phase in the aftermath of natural disasters, the government and humanitarian agencies could rebuild facilities and infrastructure including the economy of disaster victims. Central Sulawesi Assessment Institute for Agricultural Technology (AIAT) participated in the socio-economic recovery of natural disaster victims in Sigi Regency through the development of superior BALITBANGTAN (KUB) chicken based on native households in temporary shelters in Jono Oge Village, Sigi Regency. The purpose of this study was to determine the contribution and motivation of Sigi disaster victims in raising KUB chickens based on households. The contribution of raising KUB chicken was calculated from the percentage of KUB chicken to total household income while motivation was measured by the scoring method using a Likert scale. Based on the results of the assessment, it was concluded that the income of victims of natural disasters at the Jono Oge Village in Sigi Regency had contribution contribution of raising KUB chickens based on households was 8.08% categorized at <Rp1,500,000.00 and 4.21% categorize at Rp1,500,000.00 - Rp2,500,000.00. The motivation of natural disaster victims for raising KUB chickens was on the ease of sales and maintenance.